Phubbing as a social and communicative phenomenon of modernity - M. A. Yuzhanin (Путеводитель предпринимателя, 2022)
The proposed article is intended to consider an urgent and important problem — the spread among modern people of an obsessive addiction to smartphones and a frightening inability to distract from them even during a face–to–face conversation with others. The main goal of this study is to form an integral, scientifically based idea of the relevant socio–psychological and communicative phenomenon of the 21st century, called «phubbing», to analyze its distinctive features and influence on the social behavior and communication of people living in the era of digitalization. To achieve this goal, a comprehensive, interdisciplinary study of the defining characteristics and symptomatic signs of phubbing, the main approaches to the study of the causes and prerequisites for its actualization, as well as the available empirical data on the specifics and frequently occurring forms of embodiment of this phenomenon in various countries of the world is undertaken. In addition, the author focuses on the problem of so–called partner phubbing and its negative impact on a person’s close relationship with his romantic or family partner. The analysis allows us to state that in the modern information society it is very difficult for individuals to avoid strong addiction to smartphones, therefore, the social and communicative phenomenon of phubbing is likely to become an integral attribute of human life for a long time. However, the retribution for excessive attachment to communicative gadgets with a high degree of probability may be the progressive alienation of the subject from nearby relatives and friends. The solution to the problem for modern people can be the acquisition of a reasonable and harmonious combination of real and virtual, offline and online communication. It is this approach that would allow humanity to avoid digital addiction, not to lose the quality and depth of diffuse personal interactions, but rather move along the path of intellectual, emotional and communicative enrichment and self–improvement.